An Analysis of Price Competition in Heterogeneous Electric Vehicle Charging Stations - Lee, Woongsup; Schober, Robert; Wong, Vincent W. S. (IEEE Transactions on Smart Grid, 2018)
In this paper, we investigate the price competition among electric vehicle charging stations (EVCSs) with renewable power generators (RPGs). Both a large-sized EVCS (L-EVCS) and small-sized EVCSs (S-EVCSs), which have different capacities, are considered. Moreover, the price elasticity of electric vehicles (EVs), the effect of the distance between an EV and the EVCSs, and the impact of the number and type of charging outlets at the EVCSs on the behavior of EVs are taken into account. The electricity demand of the EVCSs is modeled and analyzed using a multiplicatively weighted Voronoi diagram. The price competition between EVCSs is studied by using a Stackelberg game and the electricity price is determined. Through simulations, the correctness of our analysis is validated and the payoff of the EVCSs is examined for various environments. Our results reveal that although the payoff of the EVCSs is generally small, it is higher than when the electricity from the RPGs is directly sold to the power grid. We also find that the payoff of the EVCSs is significantly affected by the elasticity of the electricity demand of the EVs. Furthermore, the payoff of the L-EVCS is inversely proportional to that of the S-EVCSs.<br
Keywords: Elasticity; Games; Electric vehicle charging; Plugs; Analytical models; Power grids; Pricing